Hubungan Lingkungan Kerja, Stres Kerja dan Kedisiplinan Kerja Terhadap Kinerja Pegawai Rumah Sakit di Daerah Pati - Griselda Ananda; Andrea Nadifa; Tansya Purnaningrum; Innocentius Bernarto (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
Background :Optimal work environment can induce productivity, affects comforts, happiness, motivation, and healthcare work performance. Work stress that is overly too high or too low could lead to decrease in work performance. Work discipline could change character, and increase awareness and availability to obey the rules of the company and its norm. The purpose of this research is to know the relationship between work environment, work stress, work discipline with performance of healthcare workers in hospitals around Pati. Method :This research utilizes a quantitative analysis approach with a Cross-Sectional design employing purposive sampling technique. Statistical analysis was conducted using multiple regression. Result: The result shows that there’s significant relationship between the work environment and performance of healthcare workers (p value= ,000 < 0,05), there’s significant relationship between work discipline and performance of healthcare workers (p value= 0,000 < 0,05), and there’s no significant relationship between work stress and performance of healthcare workers (p value= ,483 > 0,05). Conclusion : The conclusion of this research highlights the importance of the role of the work environment in shaping employee performance at Pati Hospital. Creating a positive work environment, supporting and addressing factors such as work stress, and fostering work discipline can contribute positively to improving overall employee performance and organizational effectiveness.